Maqasid al-Shari’ah dan Ijtihad Maqasidi - Abdul Majid Abror (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2020)
Maqasid al-shari’a are the final goals which must be realized by applying shari’a law which is determined by Allah for His servants regarding religious matters, whether in the form of worship or mu'amalah, which can move life human. While the shari'a laws are for the benefit of the servant, both for now and later, In relation to ijtihad maqasidi there are three elements that are interrelated with one another and have fundamental provisions that must be considered in the ijtihad process. Namely: text (nas), reality (al-waqi’) and legal subjects (al-Mukallaf).